The Influence of Product Quality and Service Quality on Customer Satisfaction in Sharia Banking (Case Study of Bank Mega Syariah Customers) - Zasalzena, Zelika; Fa’uzobihi, Fa’uzobihi; Imanudin, Kafffah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is motivated by the phenomenon of Bank Mega Syariah which has several advantages and disadvantages in the products offered. As well as the limitations of ATM machines, which is of course a weakness for BMS in providing customer satisfaction. Basically, customer satisfaction and dissatisfaction with the product will influence subsequent behavioral patterns. Likewise with the banking business, which is a business based on the principle of trust, the issue of service quality is a very important factor important in determining this success. Because whether something is successful or not       banking business depends on customer satisfaction. Providing excellent service to customers to create a good image and customer satisfaction. The higher number of customers who complain indicates that customers are not satisfied with the services provided. The aim of this research is to determine the influence of product quality and service quality on customer satisfaction in sharia banking (case study of Bank Mega Syariah customers). This research, which used quantitative methods with associative techniques, was carried out at Bank Mega Syari'ah Karawang with a population and sample of 53 Bank Mega Syari'ah employees with data collection techniques using questionnaires. The research results show that there is an influence between product quality and service quality variables on customer satisfaction which is shown by a figure of 0.383, which means that the influence contributed by product quality and service quality variables on customer satisfaction is 38.3% (R Square = 0.383) and the remaining 61.7% is influenced by other factors not examined in this study.